BORYS POPŁAWSKI I WŁADIMIR NABOKOW: DWA ŚWIATY I DWIE POETYKI - Gojło, Beata (Acta Neophilologica, 2009)
Vladimir Nabokov’s unfavourable review of Boris Poplavsky’s volume of poetry Flags becomes a starting point of presenting different ways of perceiving the world by the two artists. Their poetry reflects the vision of the world of each author. The article not only explains reasons of differences in percepting the world, which result from the authors’ youthful experiences and vicissitudes, but also states why Vladimir Nabokov, after 20 years, changed his opinion about artistic works of Boris Poplavsky.